Practice of “Defensive Medicine” Among Doctors at a Tertiary Care Hospital - Bhandari, Binus; Khadka, Dipendra; Saxena, Prem; Mishra, S.M. (Journal of Nepalgunj Medical College, 2019)
Introduction: Defensive medicine is the short term coined for a defensive medical decision making.It means advising diagnostic tests, prescribing more drugs than required or avoids treating and operating high risk patients. These may not be the best options for the patient but the practice among doctors is currently adopted to avoid litigation. A situation aggravated by the promulgation of tough consumer laws and other criminal laws applicable to health care providers. This study was conducted to assess the frequency of defensive medicine practice among doctors at the teaching medical college hospital of NGMC. Methods: A cross sectional study was conducted at Nepalgunj Medical College, Teaching Hospital, Kohalpur, a tertiary care center in between January to December 2018. A questionnaire was developed to assess the various aspects of defensive medicine practice. In this study, a total of 75 doctors participated. Results: Practice of defensive medicine was common in age between 30-40 years. Fear of caring high risk patients (76%)), ordering un-necessary tests (56%)) followed by avoiding high risk procedures (46%) were common forms of defensive medicine practices observed in sampled doctors. Senior faculties were found practicing more defensive medicine than juniors (69.4% versus 30.6%) and more in surgical field as compared to non-surgical 61% vs. 39%. Conclusion: Defensive medical practice in various ways is common among the doctors. This has produced a positive impact in the form of greater communications with the patients and awareness to have a good medical record keeping. However, the negative impacts on the doctors have been more in the form of prescribing more investigations, drugs, more referral and reluctance to accept high risk patients if there is choice.